Adrenal ganglioneuroma; a rare neurogenic tumor in a 25-year-old female - Rana, Shweta; Sharma, Puja; Garg, Shilpa; Gole, Sheetal G.; Hasija, Sonia (International Journal of Research in Medical Sciences, 2023)
Ganglioneuromas (GNs) are rare benign tumors originating from the neural crest tissue. They are characteristically located in the posterior mediastinum and retroperitoneum; and are rarely found in the adrenal gland. GNs are usually hormonally inactive, and most of the cases are detected incidentally. We report a case of 25-year-old female who presented with pain abdomen in the right upper quadrant. Imaging studies showed a large well defined hypodense lesion with calcification measuring 14.5×11.5×11cm in the region of right adrenal gland and a possibility of adrenocortical carcinoma was suggested. The patient underwent right adrenalectomy and histopathological examination revealed ganglioneuroma. This report emphasizes that GN can be misdiagnosed preoperatively as the presenting symptoms are nonspecific and imaging characteristics are variable. Histopathological examination is the mainstay of diagnosis.